Finding Providence : the story of Roger Williams - Avi, 1937- (HarperCollins Publishers, 1997)
After being forced to leave the Massachusetts Bay Colony, Roger Williams travels south and, with the help of the Narragansett Indians, founds Providence, Rhode Island.